Age-dependent myocardial transcriptomic changes in the rat. Novel insights into atrial and ventricular arrhythmias pathogenesis - Scridon, Alina; Fouilloux-Meugnier, Emmanuelle; Loizon, Emmanuelle; Perian, Marcel; Rome, Sophie; Julien, Claude; Barrès, Christian; Chevalier, Philippe (Revista română de medicină de laborator, 2014)
Background: Aging is associated with significantly increased prevalence of cardiac arrhythmias, but transcriptional events that underlie this process remain to be established. To gain deeper insight into molecular mechanisms of aging-related cardiac arrhythmias, we performed mRNA expression analysis comparing atrial and ventricular myocardium from Wistar-Kyoto (WKY) rats of different ages. Methods: Atrial and ventricular sampling was performed in 3 groups (n=4 each) of young (14-week-old), adult (25-week-old), and aging (47-week-old) WKY rats. mRNA expressions of 89 genes involved in cardiac arrhythmogenicity were investigated using TaqMan Low Density Array analysis. Results: Of the 89 studied genes, 40 and 64 genes presented steady atrial and ventricular expressions, respectively. All genes differentially expressed within the atria of WKY rats were up-regulated with advancing age, mainly the genes encoding for various K , Ca , Na channels, and type 6 collagen. Atrial expression levels of 19 genes were positively correlated with age. Ventricular transcriptomic analysis revealed a balance between up-regulated and down-regulated genes encoding for the same ion channels. Conclusion: Our results indicate the induction of an up-regulation transcriptional response in atrial but not ventricular myocytes with advancing age, suggesting that the two chambers undergo different molecular remodeling programs. Aging atria displayed a transcriptomic profile consistent with higher propensity to arrhythmias, including up-regulation of genes encoding for I , IC , IC , I , outward K+ currents, and collagen, while ventricular transcriptome did not seem to be significantly altered by aging. These observations could explain the higher propensity to atrial than ventricular arrhythmias in the elderly. Intruducere Deși înaintarea în vârstă este asociată cu creșterea prevalenței aritmiilor cardiace, evenimentele transcriptomice care stau la baza acestui proces rămân neelucidate. Pentru a identifica aceste mecanisme am realizat analiza expresiei ARNm la nivelul miocardului atrial și ventricular la șobolani Wistar-Kyoto (WKY) de diferite vârste. Metodă: Expresiile ARNm a 89 de gene au fost analizate prin TLDA utilizând eșantioane atriale și ventriculare de la 3 grupuri (n=4 fiecare) de șobolani WKY tineri, adulți și vârstnici. Rezultate: Din cele 89 de gene, 40 și respectiv 64 de gene au prezentat expresii stabile la nivel atrial și respectiv ventricular. Toate genele exprimate diferit în atriile șobolanilor WKY au prezentat o up-regulare cu înaintarea în vârstă, în special genele care codifică canale de K , Ca , Na și colagenul de tip 6. Expresia atrială a 19 gene a fost corelată pozitiv cu vârsta. Analiza transcriptomică ventriculară a evidențiat un echilibru între genele up-regulate și down-regulate codificând aceleași canale ionice. Concluzii: Rezultatele noastre indică un răspuns transcripțional atrial, dar nu și ventricular, caracterizat prin up-regulare odată cu înaintarea în vârstă. Aceste rezultate sugerează că cele două cavități sunt supuse unor programe de remodelare moleculară diferite. Atriile îmbătrânite au prezentat un profil transcriptomic sugestiv pentru o predispoziție crescută pentru aritmii, precum up-regularea genelor care codifică If, IC , IC , I și colagenul, în timp ce transcriptomul ventricular nu pare să fie sever alterat de înaintarea în vârstă. Aceste observații ar putea explica predispoziția mai mare pentru aritmii atriale decât ventriculare la vârstnici.